Takayasu Arteritis Involving Multiple Peripheral Arteries of a 37-year-old Female: A Case Report and Brief Overview (Bangladesh Heart Journal, 2016)
Takayasu arteritis, formerly known as pulseless disease, is a chronic idiopathic vasculitis which affects the large vessels in the body. First described in the 1800s, this rare condition is more commonly found in Asian women in their 40s. Herein, we report the case of a young woman whose exertional angina and claudication were the initial presentation of active Takayasu arteritis. The importance of modern technology of imaging such as CT, MRI and angiography, can often have paramount importance for confirming a diagnosis and the extent of the pathology. Newer modalities of investigation helps in evaluation of vascular involvement and its haemodynamic effects on cardiovascular system. Previously majority of patient had to be diagnosed clinically. Now a days by CT peripheral Angiogram this disease can be diagnosed. Invasive procedure of peripheral Angiogram is troublesome but single IV dye injection can revealed the actual scenario. So it has got important scientific value.Bangladesh Heart Journal 2015; 30(2) : 92-95